2014
DOI: 10.1080/15213269.2014.941112
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Transmission Processes for Information in the Emerging Media Environment: Psychological Motives and Message Characteristics

Abstract: The emerging media environment introduced fundamental changes in the quality and format of information available to the public, which can now flexibly seek, alter, and disseminate the information they receive. Therefore, the two processes of information selection and information retransmission are crucial for understanding the reach of any information available in the online information environment. From this starting point, we examine the common psychological motives driving information selection and transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 123 publications
7
128
2
4
Order By: Relevance
“…As expected by the DOI and the IMB, the social pressure created by descriptive norms (i.e., anticipating that more people in the community, including leaders, would adopt the innovation) positively predicted intentions to adopt and to maintain the SET innovation. Drawing upon social-transmission research (Berger, 2014; Cappella et al, 2015), we argued that the descriptive norm may dampen future talk about it, because it may no longer be seen as a novel, useful topic to discuss. As predicted, the results showed that as the descriptive norm increased, the intention to talk about the innovation decreased.…”
Section: Discussionmentioning
confidence: 98%
“…As expected by the DOI and the IMB, the social pressure created by descriptive norms (i.e., anticipating that more people in the community, including leaders, would adopt the innovation) positively predicted intentions to adopt and to maintain the SET innovation. Drawing upon social-transmission research (Berger, 2014; Cappella et al, 2015), we argued that the descriptive norm may dampen future talk about it, because it may no longer be seen as a novel, useful topic to discuss. As predicted, the results showed that as the descriptive norm increased, the intention to talk about the innovation decreased.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, social media have become a major marketing platform for tobacco products 24–26. New communication technologies offer alternative means for gathering and managing information, which are not present in traditional media and provide high brand visibility for tobacco products 27. The emergence of new technologies has resulted in profound changes in the media landscape and has led internet users to encounter a vast amount of online information exposure, including social exposure on social-networking sites, such as Twitter.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] New communication technologies offer alternative means for gathering and managing information, which are not present in traditional media and provide high brand visibility for tobacco products. 27 The emergence of new technologies has resulted in profound changes in the media landscape and has led internet users to encounter a vast amount of online information exposure, including social exposure on social-networking sites, such as Twitter. Twitter is particularly important as this platform is disproportionately popular among hard-to-reach populations traditionally at risk for tobacco use, such as youth and communities of colour.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal situation for persuasive reach is for people who were directly exposed to campaign messages to persuade others to comply as well. Sharing research suggests that, to satisfy impression management (Berger, 2014; Cappella et al, 2014; Kim, 2015) or defense motives (Lyons & Kashima, 2001), people share efficacious information with others, often with the intent of encouraging them to engage in action (Cappella et al, 2014). Efficacious has been defined as valuable, true, and useful (Berger, 2014; Cappella et al, 2014).…”
Section: Persuading Othersmentioning
confidence: 99%
“…Sharing research suggests that, to satisfy impression management (Berger, 2014; Cappella et al, 2014; Kim, 2015) or defense motives (Lyons & Kashima, 2001), people share efficacious information with others, often with the intent of encouraging them to engage in action (Cappella et al, 2014). Efficacious has been defined as valuable, true, and useful (Berger, 2014; Cappella et al, 2014). It is likely that information about acts judged as good, normative, and previously attempted, qualities that promote behavioral intentions according to the integrated model of behavior (Fishbein, 2000; Fishbein & Cappella, 2006), would be the kind of efficacious information people would share with others to be viewed positive, to defend their existing attitudes and actions.…”
Section: Persuading Othersmentioning
confidence: 99%